Extensions for Internet QoS paradigms to mobile IP a survey. - Taha, Abd-Elhamid M. Taha (IEEE Communications magazine)
Mobile IP has been chosen as the core mobility management mechanism for wireless LANs, 3G cellular networks, and, most recently, aeronautical networks. It is viewed as a key element in providing a universal roaming solution across different wireless access technologies. However, mobile IP in its basic form inherits the IP incapability to provide QoS guarantees. This results in mobile IP's lack of support for seamless intradomain mobility. This article surveys extensions that have been proposed to enhance the QoS functionality of mobile IP. It gives a brief overview of mobile IP and Internet QoS paradigms, and describes their general shortcomings with regard to QoS and mobility, respectively. It then discusses the extensions that have been proposed in the literature and provides a qualitative comparison.